KEAKTIFAN IBU DALAM PIJAT BAYI TERHADAP LAMA TIDUR - Dian Puspita Yani; Sri Banun Titi Istiqomah; Muzayyaroh Muzayyaroh; Dewi Triloka Wulandari; Sabrina Dwi Prihatini; Pujiani Pujiani (Jurnal Keperawatan Muhammadiyah, 2023)
Objective: This study aims to determine the activeness of mothers to do baby massage to the length of sleep in babies aged 7-12 months in Ngumpul village, peterongan district, jombang regency in 2022.Methods: The method used in the study was analytic with a cross sectional approach by two variables; the mother's activeness in baby massage and the length of sleep of babies aged 7-12 months with 30 respondents who had babies aged 7-12 months during April - May 2022. A questionnaire is used as the tool in collecting the data. The questionnaire consists of 2 parts, namely the respondent's questionnaire to find out the identity of the respondent, and a true or false questionnaire as an observation sheet consisting of 15 questions. Meanwhile, to determine the relationship between the two variables, the Spearman Correlation statistical test was used with the help of the SPSS 13 Statistical Test. The level of probability in this study is if α ≤ 0.05 then H0 is rejected and H1 is accepted, meaning that there is a relationship between the mother's activeness in baby massage and the length of baby's sleep.Results: The results of this study show that there is a correlation between the two variables, meaning that there is a relationship between the activeness of mothers doing baby massage and the length of baby's sleep. The more often the mother does the massage, the longer the baby's sleep will be and the better the quality of sleep. This can be one of the treatments to optimize the growth and development of babies.Conclusion: Baby massage can make babies sleep longer so that the baby's growth and development can run optimally